(untitled) (مجلة المنصور, 2022)
The drug of all kinds have damaged social, economic and moral, mental and disruption of manpower in the country, bringing traffic and smuggled weapon resort discount to destroy human capabilities and the social and economic sectors important people, so that the face of those dangerous scourge necessity dictated by the duty to maintain the values and energies people looking forward to construction and development, development and maintain the capacity and vitality of his youth, and they are a pillar of this building. And began combating the world drug policy national criminal founded on criminal law and its tool, police and customs and border guards, and the first released in Iraq is the law preventing cultivation hemp hashish Indian opium poppy No. (12) 1933, and the Dangerous Drugs Act and narcotic (44) 1938, and its amendments and the remaining systems The data and instructions issued pursuant thereto until a window replaced. And those laws were canceled and replaced by Iraqi Drug Law No. (68) 1965.